Reactions to ideal body shapes. Issue 4 (1st October 2020) - Prnjak, Katarina; Pemberton, Stephanie; Helms, Eric; Phillips, James G.
Abstract: Difficult-to-attain beauty standards that are promulgated by the media could contribute to body dissatisfaction, but their potential impact upon body image remains unclear. The present study examined reactions to thin-ideal and muscular-ideal images, and examined the effects of ideal image exposure on preferred body shape and time spent deliberating about ideal shape. In a 2 × 2 experimental design, 200 Internet users completed the Kessler psychological distress scale (K10) and were randomly assigned to view idealistic body images or houses (and rated them on semantic differential dimensions). Females viewed thin ideal images and males viewed muscular ideal images, while the control groups viewed images of houses. Between group measures analysis of variance revealed women reacted negatively to thinspirational images. Women were more driven for thinness and idealized a thinner shape for the female body than men. Psychologically distressed participants had a stronger drive for thinness and greater body dissatisfaction compared to low-distress participants. In addition, although beauty ideal imagery had no significant impact on males, females spent more time in choosing ideal body figure. Viewing thin bodies for females created a trend toward desiring a slimmer figure, as well as increased preoccupation with size as they spent more time deliberating over a photorealistic figure rating scale. Therefore, exposure to thinspiration promotes dissatisfaction with self and leads women to dwell more upon their body image.